2021
DOI: 10.1177/1744987121991417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an evidence-based practice mentorship programme in a paediatric quaternary care setting

Abstract: Background Evidence-based practice (EBP) is essential for clinical decision-making, improving care, reducing costs and achieving optimal patient outcomes. The Evidence-based Practice Mentorship Program (EBPMP) is a flexible, self-directed programme whereby participants carry out EBP projects guided by expert mentors. Aims To evaluate EBPMP effectiveness and participant experience. Methods To evaluate effectiveness, as measured by changes in EBP value, knowledge and implementation, participants completed pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Reliability was not assessed in three studies (Bajracharya et al, 2019; Dao et al, 2018; McCluskey, 2003). Belowska et al (2020) and Schuler et al (2021) reported that this has been confirmed in a previous study. Validity was confirmed using content (Dao et al, 2018; Filippini et al, 2011; Fu et al, 2020; Majid et al, 2011) and construct validity (Fu et al, 2020).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Reliability was not assessed in three studies (Bajracharya et al, 2019; Dao et al, 2018; McCluskey, 2003). Belowska et al (2020) and Schuler et al (2021) reported that this has been confirmed in a previous study. Validity was confirmed using content (Dao et al, 2018; Filippini et al, 2011; Fu et al, 2020; Majid et al, 2011) and construct validity (Fu et al, 2020).…”
Section: Resultssupporting
confidence: 77%
“…The studies were conducted in 17 countries: 12 in the USA (Brown et al, 2009; Ginex et al, 2021; Jette et al, 2003; Koehn & Lehman, 2008; Maydick‐Youngberg et al, 2021; Melnyk et al, 2018, 2020; Nickles et al, 2019; Schuler et al, 2021; White‐Williams et al, 2013; Williamson et al, 2015; Wonder et al, 2017), four in Iran (Azmoude et al, 2017; Heydari et al, 2014; Seyyedrasooli et al, 2012; Shafiei et al, 2014), three in Brazil (Claudino et al, 2019; Schneider et al, 2020; Silva et al, 2015) and China (Fu et al, 2020; Yue et al, 2018; Zhou et al, 2016), two each in Oman (Al‐Busaidi et al, 2019; Ammouri et al, 2014), Saudi Arabia (Alqahtani et al, 2020; Alshehri et al, 2017), Finland (Koota et al, 2021; Lunden et al, 2021) and Spain (Pérez‐Campos et al, 2014; Ramos‐Morcillo et al, 2021), one each in Nepal (Bajracharya et al, 2019), Poland (Belowska et al, 2020), Vietnam (Dao et al, 2018), Italy (Filippini et al, 2011), Singapore (Majid et al, 2011), Greece (Patelarou et al, 2017), Colombia (Ramírez‐Vélez et al, 2015), Jordania (Salah & Abu‐Moghli, 2020) and Australia (McCluskey, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations